Epidemiological situation of leishmaniasis during the period 2020-2024 in the province of Ouezzane Northern Morocco - Youssef, EL GHRIFI; Abdellah, EL ZHIRI; Nouhaila, BELGHYTI; ELKHARRIM, Khadija; BELGHYTI, Driss (Edelweiss Applied Science and Technology, 2025)
Leishmaniasis is a parasitic disease caused by protozoa of the genus Leishmania, transmitted to humans through bites of infected sandflies. In Morocco, this disease remains a significant public health concern, with an uneven distribution across different regions. The province of Ouezzane, situated in northern Morocco and characterized by mountainous terrain, a sub-humid climate, and a predominantly rural population, provides an environment conducive to the maintenance and transmission of leishmaniasis. Therefore, studying the epidemiological situation of leishmaniasis in Ouezzane is crucial not only for understanding the dynamics of disease transmission but also for guiding effective prevention and control strategies. An epidemiological study conducted in Ouezzane between 2020 and 2024 indicates a predominant occurrence of cutaneous leishmaniasis, accounting for 97.7% of cases, over the visceral form. The disease primarily affects rural areas, with notable outbreaks in Teroual, Zghira, and Sidi Bousber. Lesions are mainly located on the face and typically present as a single lesion, suggesting the predominance of Leishmania major. In contrast, multiple lesions, which are less common, may indicate the presence of Leishmania tropica. The disease mainly impacts children aged 0–14 years and, to a lesser extent, women. However, it is expected that by 2024, the gender distribution will become more balanced. Over the five-year period, the number of cases has doubled, reflecting both increased awareness and improved screening efforts, largely due to campaigns organized by the Ministry of Health.